Ischemia Reperfusion Injury Triggers CXCL13 Release and B-Cell Recruitment After Allogenic Kidney Transplantation - Kreimann, Kirill; Jang, Mi-Sun; Rong, Song; Greite, Robert; von Vietinghoff, Sibylle; Schmitt, Roland; Bräsen, Jan Hinrich; Schiffer, Lena; Gerstenberg, Jessica; Vijayan, Vijith; Dittrich-Breiholz, Oliver; Wang, Li; et al. (Frontiers in Immunology, 2020)
Ischemia reperfusion injury (IRI) is linked with inflammation in kidney transplantation (ktx). The chemokine CXCL13, also known as B lymphocyte chemoattractant, mediates recruitment of B cells within follicles of lymphoid tissues and has recently been identified as a biomarker for acute kidney allograft rejection. The goal of this study was to explore whether IRI contributes to the up-regulation of CXCL13 levels in ktx. It is demonstrated that systemic levels of CXCL13 were increased in mouse models of uni- and bilateral renal IRI, which correlated with the duration of IRI. Moreover, in unilateral renal IRI CXCL13 expression in ischemic kidneys was up-regulated. Immunohistochemical studies revealed infiltration of CD22+ B-cells and, single-cell RNA sequencing analysis a higher number of cells expressing the CXCL13 receptor CXCR5, in ischemic kidneys 7 days post IRI, respectively. The potential relevance of these findings was also evaluated in a mouse model of ktx. Increased levels of serum CXCL13 correlated with the lengths of cold ischemia times and were further enhanced in allogenic compared to isogenic kidney transplants. Taken together, these findings indicate that IRI is associated with increased systemic levels of CXCL13 in renal IRI and ktx.